Genomic Research to Identify Novel Pathways in the Development of Abdominal Aortic Aneurysm - Seamus C. Harrison; Anastasia Z. Kalea; Michael V. Holmes; Obi Agu; Steve E. Humphries (Cardiology Research and Practice)
Abdominal aortic aneurysm (AAA) is a common disease with a large heritable component. There is a need to improve our understanding of AAA pathogenesis in order to develop novel treatment paradigms. Genomewide association studies have revolutionized research into the genetic variants that underpin the development of many complex diseases including AAA. This article reviews the progress that has been made to date in this regard, including mechanisms by which loci identified by GWAS may contribute to the development of AAA. It also highlights potential post-GWAS analytical strategies to improve our understanding of the disease further.